Allergic contact dermatitis due to topical minoxidil solution. - Foti, C. (European Journal of Pediatric Dermatology, 2017)
Minoxidil is the only FDA-approved topical therapy for androgenetic alopecia therapy. Like any long-term topical drug may be responsible for side effects, especially itching and scaling but also telogen effluvium (2). These symptoms can be caused by contact allergy to minoxidil, more commonly with the use of the 5% solution (1). The same symptoms can be due more frequently to contact allergy to propylene glycol excipient or can be due to irritant contact dermatitis or to exacerbation of previous seborrheic dermatitis. To differentiate these conditions it is necessary for the patient to perform patchs tests with minoxidil and propylene glycol. In the case of propylene glycol allergy, minoxidil may be continued by using another excipient, for example butylene glycol.